Default-mode network changes in preclinical Huntington's disease - Wolf, Robert Christian; Wolf, Nadine D.; Thomann, Philipp (Experimental neurology, 2012)
The default-mode network (DMN) refers to as a set of brain regions which are active when the brain does not engage in a cognitive task and which are deactivated with task-related cognitive effort. Altered function of the DMN has been associated with a decline of cognition in several neurodegenerative diseases and related at-risk conditions. In Huntington's disease, an autosomal dominant inherited neurodegenerative disorder, several studies so far have shown abnormal task-related brain activation patterns even in preclinical carriers of the Huntington's disease gene mutation (preHD). To date, however, the functional integrity of the DMN has not been addressed in this population. The aim of this study was to study the functional connectivity of the DMN in 18 preHD and 18 healthy controls who underwent functional magnetic resonance imaging during an attention task. A group independent component analysis identified spatiotemporally distinct patterns of two DMN subsystems. The spatial distribution of these components in preHD was similar to controls. However, preHD showed lower subsystem-specific connectivity in the anterior medial prefrontal cortex, the left inferior parietal and the posterior cingulate cortex (p<0.05, cluster-corrected). Connectivity between the two DMN subsystems was increased in preHD compared to controls. In preHD individuals lower functional connectivity of the left inferior parietal cortex was associated with shorter reaction times in the attention task. This suggests that some functionally critical regions of the DMN may have to remain active to maintain or optimise cognitive performance in preHD.
Available online 25 June 2012
Gesehen am 15.10.2018
Available online 25 June 2012